The use of Xitsonga at the University of Limpopo (Turfloop Campus) - Nkwashu, Delina; Madadzhe, Richard Ndwayamato; Jubayi, Sikhetho Joe (South African Journal of Higher Education, 2016)
This article examines the acceptability of Xitsonga as a medium of instruction and learning at the University of Limpopo. Currently, English dominates the higher education environment because almost all the universities in South Africa utilise it as a medium of instruction for teaching and learning. In addition, English is extremely popular in higher education because it is viewed as the language of the corporate world as well as the language of science. In such a context, the article sets out to determine whether the introduction of Xitsonga as a medium of instruction and learning would be tenable and desirable at the aforementioned university. The data collected indicate that the majority of Xitsonga speakers believe that Xitsonga should not be used as a medium of instruction in tertiary education. It is concluded, however, that mother tongue education enhances, rather than diminishes learning, including the learning of additional languages.